Suplementasi Mineral Cu dan Zn dalam Pakan terhadap Organ Dalam dan Lemak Abdomen Ayam Broiler: Effect of Supplementation of Copper and Zinc in Feed on Giblets and Abdominal Fat of Broilers - R Lestari; A Darmawan; Indah Wijayanti Wijayanti (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2020)
This experiment was design to evaluate the effects of supplementation of Zn and Cu in inorganic or organic form on broiler’s percentage of giblets and abdominal fat of 35-day-old broiler chickens. The experiment used a completely randomized design with two treatments, 17 replicates and 32 birds per pen (816 female and 272 male). The treatments based on the type of mineral i.e. inorganic (T1) and organic (T2). The types of mineral did not affected the weight and percentage of weight of bursa fabricius, lymph, heart, bile gland, kidney, and abdominal fat. The types of mineral did not affected the weight of thymus, liver, proventriculus, pancreas, and gizzard, but were affected their percentage of weight (p<0.05). The types of mineral were affected the length and percentage of weight of duodenum, jejunum,and ileum (p<0.05) . The types of mineral were affected the length of secca, but did not affected its percentage of weight (p<0.05). The types of mineral did not affected the length of colon, but were affected its percentage of weight (p<0.05). The supplementation of mineral Cu and Zn in organic form has better absorption of nutrient and positive effect to health of chickens in stress due to heat stress. Key words: broiler, copper, inorganik mineral, organik mineral, zinc